Samfunnsøkonomiens plass i jussen: Det juridiske fakultets første hundre år - Halvor Mehlum (University of Oslo, Department of Economics, 2013)
– In this article I take up the relationship between economics and law in the hundred-year period preceding the establishing of economics as a separate discipline. Rather than providing a review of historical milestones, I concentrate on some observations that illustrate the relationship between law and economics. I conclude with some reflections on what the law may have missed out on by not having participated in a similar revolution as economics experienced.
Keywords: B1; K00; 330